2017
DOI: 10.1111/bph.13861
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide pretreatment improves mitochondrial function in myocardial hypertrophy via a SIRT3‐dependent manner

Abstract: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 69 publications
9
81
2
2
Order By: Relevance
“…DRP1 is a core component for mitochondrial fission, while OPA1 is as a fusion‐associated protein . These two proteins have been proposed as novel therapeutic targets for maintaining a physiological redox . Our present study found that NaHS reduced DRP1 but increased OPA1 expression in both skin wound and scratched skin fibroblasts.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…DRP1 is a core component for mitochondrial fission, while OPA1 is as a fusion‐associated protein . These two proteins have been proposed as novel therapeutic targets for maintaining a physiological redox . Our present study found that NaHS reduced DRP1 but increased OPA1 expression in both skin wound and scratched skin fibroblasts.…”
Section: Discussionsupporting
confidence: 59%
“…DRP1 is a mitochondrial fission‐associated protein, while OPA1 is a mitochondrial fusion‐associated protein . Both DRP1 and OPA1 play important roles in mitochondrial function and ROS production . We found that NaHS significantly decreased DRP1 but increased OPA1 protein expression in the tissues from the wound area (Figure C).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Celastrol is a pentacyclic triterpenoid compound (the chemical structure of celastrol is shown in Figure ), which is isolated from a common clinical used Traditional Chinese Medicine named Tripterygium wilfordii Hook F. Celastrol possesses multiple pharmacological effects and showed potent anti‐inflammatory effect against many disease models, and however, few reports can be seen regarding the anti‐inflammatory potential of celastrol in liver fibrosis. SIR2 is a family of histone deacetylases and is widely distributed in cells with multiple functions . A total of seven members (SIRT1‐SIRT7) have been identified in mammalian .…”
Section: Introductionmentioning
confidence: 99%